Variation of Wheat Genotypes in Calcareous Soil as Affected by Root Growth and Mycorrhizal Hyphae– A Mechanistic Modeling Approach. Issue 8 (27th April 2020) - I. I., Abou El Seoud; El Adly, R. M.; Sadik, M.W.; Moghanm, F.S.
ABSTRACT: This experiment aimed to study phosphorus efficiency of six wheat genotypes ( Triticum aestivum ) inoculated with arbuscular mycorrhizal fungi (AMF) and to quantify the contribution of root and mycorrhizal hyphae length to P uptake by using NST 3.0 model. The results showed that all wheat genotypes with AMF (except V4) attained more than 80% of the maximum shoot yield. NST 3.0 predicted approximately 49% and 30% of observed P uptake for V4 with and without mycorrhizae, respectively, at the lowest P level. Additionally, the predicted values of P uptake increased rapidly with increasing P levels by up to 90% and 89% with and without mycorrhizae, respectively, at the highest P level. The model predicted 58% and 43% of the observed P uptake for V6 with and without mycorrhizae, respectively, at the lowest P level and increased up to 98% and 95% respectively at the highest P level. Soil P depletion zones of plants without mycorrhizal fungi (V4 and V6) did not extend as far as those of plants with mycorrhizal fungi. In conclusion, we recommend that V6 (Gemmeiza12) is suitable for growth in calcareous soil with or without mycorrhizal fungi inoculation (highly P efficient). The results of this study suggest that root growth and mycorrhizal hyphae length are the main parameters suitable for selecting P-efficient wheat genotypes, especially under limited P supplies. The current study clearly shows that (NST 3.0) model provide useful tools for studying the role of (AMF) and root length in plant P uptake.